Identification of two ferritin genes and their expression profiles in response to bacterial challenge in noble scallop Chlamys nobilis with different carotenoids content. Issue 88 (May 2019) - Zhang, Hongkuan; Cheng, Dewei; Tan, Karsoon; Liu, Hongxing; Ye, Ting; Li, Shengkang; Ma, Hongyu; Zheng, Huaiping
Abstract: As a major intracellular iron storage protein, ferritin plays important roles in iron homeostasis and innate immunity. In this study, two novel ferritin subunits from noble scallop Chlamys nobilis ( CnFer1 and CnFer2 ) were identified and analyzed. The open reading frame of CnFer1 and CnFer2 was 522 and 519bp long, encoding 173 and 172 amino acids, respectively. Both ferritins contained a putative iron-binding region signature (IBRS). Analysis of putative conserved domains showed the two CnFer genes contained three key domains of ferritin subunits, a ferroxidase diiron center (E25, Y32, E59, E60, H63, E105, and Q139), an iron ion channel (H116, D129, E132) and a ferrihydrite nucleation center (D58, E59, and E62) that present in M type subunits. A putative iron response element (IRE) was observed at both CnFer genes in the 5' UTR. Phylogenetic analysis result suggested that the two genes are cytoplasmic ferritins and have the closest evolution relationship with ferritins from Mizuhopecten yessoensis . The two ferritin genes were wildly expressed in examined tissues and the highest level was found in gill. After V. parahaemolyticus challenged, both CnFer genes were significantly up-regulated suggesting that they are important proteins involved in host immune defense. Moreover, under bacterial challenge, the expression levels of both two genes in Golden scallops (rich in carotenoids) were significantly higher than that in Brown scallops (less in carotenoids) which suggesting that carotenoids enhance the immunity in scallops to defense against the bacterial stress. Highlights: Bioinformatics of CnFer genes were analyzed. Golden and Brown scallops were acutely challenged by V. parahaemolyticus. CnFer genes expression level was significantly up-regulated in hemocytes and gill. Carotenoids enhance the immunity in scallop to defense against the bacterial stress by up-regulating gene expression level.